2015
DOI: 10.1007/s11060-015-1882-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in functional MRI signals after 3D based radiotherapy of glioblastoma multiforme

Abstract: The purpose of our study was to examine the potential effects of conventional 3D based radiotherapy on functional MRI activation areas following the treatment of glioblastoma multiforme. Seventeen patients with a histologically proven glioblastoma multiforme were enrolled in this study. A functional MRI examination was performed alongside the planning CT and conventional MRI prior to the delivery of conventional 3D based radiotherapy. All patients received 3D based postoperative radiotherapy (up to 60 Gy) comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Aside from that, several patients in this study had already undergone previous therapies. Alterations in fMRI signals [ 40 ], as well as FC, might be induced by both chemotherapy [ 41 , 42 , 43 ] and radiotherapy [ 44 , 45 ]. Moreover, a possible explanation for altered FC in the presence of BM could also be cerebral reorganization [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from that, several patients in this study had already undergone previous therapies. Alterations in fMRI signals [ 40 ], as well as FC, might be induced by both chemotherapy [ 41 , 42 , 43 ] and radiotherapy [ 44 , 45 ]. Moreover, a possible explanation for altered FC in the presence of BM could also be cerebral reorganization [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics enables high-output extraction of medical image quantitative features, providing a comprehensive non-invasive assessment of tumor phenotype [42]. Radiomics has spurred interest in near-term research initiatives that include photon and particle radiotherapy delivery platforms driven by treatment planning software utilizing (a) biologic rather than physical dose [43], (b) grid therapy [44], and (c) avoidance algorithms for eloquent brain [45]. How best to integrate radiomics into clinical trials remains under study.…”
Section: New Complimentary Tools and Clinical Methods In Management Omentioning
confidence: 99%
“…Functional MRI, which indirectly measures neural activity through the measurement of changes in blood flow, has observed that after high radiotherapy doses there is a decrease in neural activation during motor and sensory tasks that lasts several months [ 124 ]. Moreover, MR spectroscopy has reported a molecular derangement not only in areas of the brain receiving high doses of radiotherapy, but also in unexposed regions [ 125 , 126 ], probably related to a release of cytokine cascades.…”
Section: New Approaches To Investigate Neurotoxicity From Treatmentsmentioning
confidence: 99%